Akibat Hukum Penyalahgunaan Surat Kuasa Melampaui Kewenangan yang Diberikan Berdasarkan Hukum Perdata di Indonesia (Putusan Pengadilan Cirebon Nomor 104/PDT.G/2012/PN.Cbn) - Andryawan Andryawan; Sakthi Rahayu Setia N; Arnold Arnold; Alfin Prananda Widianto (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
In modern life, buying and selling activities typically involve three main parties: the first party as the seller, the second party as the buyer, and the third party, who may act as a witness or guarantor. Given the involvement of multiple parties, it is often necessary to issue a power of attorney to ensure the smoothness and legality of the transaction process. However, abuse of authority under the granted power of attorney frequently occurs, as seen in Cirebon District Court Case No. 104/PDT.G/2012/PN.Cbn. This study explores the legal consequences of abuse of authority under a power of attorney, focusing on the Cirebon District Court Case No. 104/PDT.G/2012/PN.Cbn. The research employs a normative juridical method to examine relevant legal regulations and principles of Indonesian civil law. The findings indicate that acts by an attorney that exceed the scope of the granted authority can render the power of attorney null and void by law, and the defendant’s actions of selling the plaintiff’s land, exceeding the authority of the power of attorney, may be deemed a violation that harms the principal. Furthermore, such abuse also creates legal uncertainty for the parties involved. These findings reinforce the importance of limiting powers in order to maintain legal certainty and protect the principal. In conclusion, there is a need for supervision and regulatory updates in the use of powers of attorney in Indonesia to prevent abuse.